Persistence length of α-helical poly-l-lysine. Issue 35 (30th August 2022) - Wilcox, Kathryn G.; Dingle, Marlee E.; Saha, Ankit; Hore, Michael J. A.; Morozova, Svetlana
Abstract : The α-helix has a significant role in protein function and structure because of its rigidity. Abstract : The α-helix has a significant role in protein function and structure because of its rigidity. In this study, we investigate the persistence length, l p, of α-helical poly-l -lysine, PLL, for two molecular weights. PLL experiences a random coil–helix transition as the pH is raised from 7 to 12. Using light scattering experiments to determine the radius of gyration ( R g ), hydrodynamic radius, ( R h ), the shape factor ( R g / R h ), and second virial coefficient ( A 2 ), and circular dichroism to determine the helical content, we find the structure and l p of PLL as a function of pH (7.4–11.4) and ionic strength (100–166 mM). With increasing pH, we find an increase in l p from 2 nm to 15–21 nm because of α-helix formation. We performed dissipative particle dynamics (DPD) simulations and found a similar increase in l p . While this l p is less than that predicted by molecular dynamics simulations, it is consistent with other experimental results, which quantify the mechanics of α-helices. By determining the mechanics of helical polypeptides like PLL, we can further understand their implications to protein function.